2018
DOI: 10.1016/j.pbb.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isolated tobacco alkaloids and tobacco products on deprivation-induced food intake and meal patterns in rats

Abstract: The ability of smoking to reduce body weight serves as motivation for continued smoking. It is unclear to what extent non-nicotine constituents in cigarettes are contributing to the weight-reducing effect of smoking. The purpose of the current study was to examine the effects of nicotine and four minor tobacco alkaloids (nornicotine, cotinine, anatabine, and anabasine) on food intake, one of the key regulators of body weight. In addition, a smokeless tobacco extract (STE) and e-cigarette (EC) refill liquid wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…There are as yet relatively few studies of the effects of ENDS in rodent models, however, recent studies showed e-cigarette based vapor inhalation of nicotine in mice reduced body temperature and locomotor activity (Lefever et al, 2017) and increased platelet activity (Qasim et al, 2018), which together demonstrate the feasibility of the approach. The paucity of models is underlined by the fact that several recent studies have resorted to parenteral injection of e-cigarette refill liquids to determine effects in rats (Bunney et al, 2018;El Golli et al, 2016;Golli et al, 2016;Harris et al, 2015;LeSage et al, 2016). Inhalation administration of nicotine is possible since one study showed that inhalation of air bubbled through an aqueous solution of nicotine produces nicotine dependence and facilitates the acquisition of subsequent nicotine intravenous self-administration (Gilpin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There are as yet relatively few studies of the effects of ENDS in rodent models, however, recent studies showed e-cigarette based vapor inhalation of nicotine in mice reduced body temperature and locomotor activity (Lefever et al, 2017) and increased platelet activity (Qasim et al, 2018), which together demonstrate the feasibility of the approach. The paucity of models is underlined by the fact that several recent studies have resorted to parenteral injection of e-cigarette refill liquids to determine effects in rats (Bunney et al, 2018;El Golli et al, 2016;Golli et al, 2016;Harris et al, 2015;LeSage et al, 2016). Inhalation administration of nicotine is possible since one study showed that inhalation of air bubbled through an aqueous solution of nicotine produces nicotine dependence and facilitates the acquisition of subsequent nicotine intravenous self-administration (Gilpin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There are as yet relatively few studies of the effects of ENDS in rodent models, however recent studies showed e-cigarette based vapor inhalation of nicotine in mice reduced body temperature and locomotor activity (Lefever et al 2017) and increased platelet activity (Qasim et al 2018), which together demonstrate the feasibility of the approach. The paucity of models is underlined by the fact that several recent studies have resorted to parenteral injection of e-cigarette refill liquids to determine effects in rats (Bunney et al 2018;El Golli et al 2016;Golli et al 2016;Harris et al 2015;LeSage et al 2016). Inhalation administration of nicotine is possible, since one study showed that inhalation of air bubbled through an aqueous solution of nicotine produces nicotine dependence and facilitates the acquisition of subsequent nicotine intravenous self-administration (Gilpin et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…20,000/month. It has been reported that nicotine in tobacco reduces the appetite12, so people with low incomes might use tobacco products to suppress their appetites, ultimately leading to the development of HNSCC.…”
Section: Discussionmentioning
confidence: 99%